PEMANFAATAN BULU AYAM DAN KOMPOSISI CANGKANG RAJUNGAN UNTUK MENINGKATKAN KUALITAS FISIK DAN KIMIA KOMPOS - Kusmiadi R; Khodijah NS; Akbar A (Program Studi Agroteknologi, Fakultas Pertanian, Fakultas Pertanian, Perikanan dan Biologi Universitas Bangka Belitung, 2014)
Utilization of waste chicken feather and crab shells as compost material is an alternative to reduce the environmental pollution caused by waste. This research is identify and study the effect of the addition of crab shells during composting of chicken feather in improving the physical and chemical quality compost chicken feather. The composition compost consists of 1.75 kg of chicken feathers + 0.15 kg of chicken manure + 0.1 kg bran. Treatment includes research R0 without the addition of crab shells, R1 0,2 kg, R2 0,4 kg, R3 0.6 kg shell crab. This research used a cluster randomized design (RAK) consisting of 4 treatment, which was repeated 3 and each treatment has 3 samples, 36 samples were obtained observations. Observations on the observed variables were analyzed using the F test. If there is a treatment that have a real effect, it will continue to use further testing Honestly Significant Difference (HSD) with a 95% confidence level. Physical parameters include is water conten, temperature, and colour of compost. Parameters chemical include is N, P, K, Ca, C- Organik, and C/N ratio. The results showed that the addition 0.6 kg of crab shells only give the effect in improving quality pH (7,29%), Ca (6,8%), P (1,16%), N-Total (4,16%). Variables that have met quality standards by SNI 19-7030-2004 compost is N-total, pH, Ca, C-Organic and Phosphorus